Histamine H1 receptors identified in mammalian brain membranes with [3H]mepyramine. - Tran, V T (1978)
The antihistamine [3H]mepyramine binds to H1 histamine receptors in mammalian brain membranes. Potencies of H1 antihistamines at the binding sites correlate with their pharmacological antihistamine effects in the guinea pig ileum. Specific [3H]mepyramine binding is saturable with a dissociation constant of about 4 nM in both equilibrium and kinetic experiments and a density of 10 pmol per gram of whole kinetic experiments and a density of 10 pmol per gram of whole brain. Some tricyclic antidepressants are potent inhibitors of specific [3H]mepyramine binding. Regional variations of [3H]mepyramine binding do not correlate with variations in endogeneous histamine and histidine decarboxylase activity.